The Pediatric Patella: Normal Development, Anatomical Variants and Malformations, Stability, Imaging, and Injury Patterns - Maloney, Ezekiel; Stanescu, A. Luana; Ngo, Anh-Vu; Parisi, Marguerite T.; Iyer, Ramesh S. (Seminars in Musculoskeletal Radiology, 2018)
We discuss the pediatric patella, with an emphasis on diagnostic imaging. Topics include normal patellar development, anatomical variants and their physiologic significance, genetic syndromes that alter the appearance of the patella, physiology of patellar tracking and stability, patellofemoral instability, and injury patterns and classification. Recognition of appropriate development on imaging prevents diagnostic error and unnecessary evaluation. Knowledge of the pertinent features of syndromes associated with morphological patellar abnormalities can aid in generating a succinct and relevant differential diagnosis. In patellofemoral instability, the patient's baseline anatomy, factors that predispose to instability, and the specific injuries that occur as a result are critical considerations for determining the course of treatment. Patellar sleeve fractures are unique to pediatric patients, and timely identification is critical to achieving an optimal treatment outcome.
Keywords: pediatric patella; imaging; variants; instability; injuries